Análise da trilha musical da minissérie A Casa das Sete Mulheres - Jefferson Tiago de Souza Mendes da Silva (2014)
The composer Marcus Viana is responsible for the soundtrack of the miniseries A Casa das Sete Mulheres (2003), sixty-six songs present in this TV drama. This amount of songs, fifty-eight are of his authorship or co-authorship. As in any other soundtrack - present in the opening vignette, the themes of the main characters in the soundscapes and the ambient music - have as their main function is to enchant and transport viewers to the scenes. Of the seven main characters, it is identified that only five songs had themes, three of authorship or partnership with composer Marcus Viana and the other two of Flávio Venturini and Jorge Vercílio. This research was based on the approach of Musical Paradigmatic Analysis of Jean-Jacques Nattiez (1990) and sought to study the musical language of the five themes of the songs main of the miniseries. The analyzes showed that, in some passages, composers (Marcus Viana, Flávio Venturini and Jorge Vercílio) use the same melodic line, rhythmic and tonal coloring it without great contrasts.